STRUKTUR MODAL DAN VARIABEL YANG MEMPENGARUHINYA - Denny Asmas; Hasminidiarty Hasminidiarty; R Adisetiawan (J-MAS (Jurnal Manajemen dan Sains), 2018)
This research aims to analyze the factors affecting the capital structure of the company. The sample companies are companies incorporated in the Indonesia Stock Exchange's LQ45 period 2012-2017. Bound variable used in this research is the structure of assets, while non used is the company's size, profitability, liquidity, operating leverage and sales growth. Test tool used multiple regression test tools IE. The results obtained i.e. There are five free variables that influence partially against variable capital structure i.e. variable structure of assets, company size, profitability, liquidity and sales growth. While the operating leverage variable have no effect partially against the capital structure.